The Collected Mathematical Papers of Arthur Cayley Volume . 8

The Collected Mathematical Papers of Arthur Cayley Volume . 8

By (author) 

List price: US$11.16

Currently unavailable

Add to wishlist

AbeBooks may have this title (opens in new window).

Try AbeBooks

Description

This historic book may have numerous typos and missing text. Purchasers can usually download a free scanned copy of the original book (without typos) from the publisher. Not indexed. Not illustrated. 1895 edition. Excerpt: ...to write down the values of x, x, the mode of obtaining these being already explained. The 52 Cases for the in-and-circwmscribed triangles. Case 1. No identities. x = BcDeFa, x'= FeDcBa (= x), g = 2aceBDF. Case 2. a = c = x. x = B(x-)DeFx, x' = FeDxB (x-1) (= x), g = 2x(x-)eBDF. Second process, for form a = e = x. The equation of correspondence is here g-XX+F(e-e-e') = 0; but the points e being given as all the intersections of the curve a(=e) by the linesystem cDe which does not pass through a, we have e--e--e' = 0; so that g = X + X; and then x = BcDxF(x-l), x' = F(x-l)DcBx, giving the former result). Case 3. D=F=x. Reciprocation from 2; or else, second process, x = BcXe(X-)a, X = Xe(X-l)cBa, g = 2X(X-l)Bace. Third process: form F= B=x. We have here g = X + X--Red. x-XcDeXa, = XeDcXa (= x), x + X'=2XDace; and the reductions are those of the first and second mode, as explained ante, Nos. 11, 12, viz. each of these is = XDace, and together they are = 2XDace; whence the foregoing result. Case 4. a = D=x. x = BcXeFx, x = FeXBx (= x), g = 2XxceBF. 1 Of course, the result is obtained in the form belonging to the new form of specification, viz. here it is = 2x x-1) cBDF; and so in other instances; but it is unnecessary to refer to this change. Observe this is what the result for Case 1 becomes on writing therein a = D=x, viz. the opposite curves a, D may become one and the same curve without any alteration in the form of the result. Case 5. a = B--x. X = (X-2)cDeFx, x' = FeDcX (x-2), where (X-2)x + X(x-2) = 2(Xx-X-x); therefore g = 2(Xx-X x)ceDF. Case 6. a = c = e = x: perhaps most easily by reciprocation of Case 7; or Second process, functionally by taking the curve a = c=e to be the aggregate curve x + at. The triangle aBcDeF is here in...show more

Product details

  • Paperback | 132 pages
  • 189 x 246 x 7mm | 249g
  • Rarebooksclub.com
  • United States
  • English
  • black & white illustrations
  • 1236837991
  • 9781236837998